Strategy of Development of Socially Oriented Business Environment of Lviv - Melnyk, M.I. (Економічний вісник Донбасу, 2013)
In the article strategic priorities and recommendations concerning formation and development of sociallyoriented business-environment are substantiated; author’s concept on formation of a socially-oriented businessenvironment is offered, which is based on the definition of its system characteristics, levels, principles, criteria, prerequisites. The development strategy of sociallyoriented business environment contains organizational and economic instruments promoting social responsibility and solidarity of business, government and society, and enhance the prestige of institutionalization of socially responsible standards of behavior of economic agents.